Incidencia del margen de contribución en la toma de decisiones gerenciales de empresas panificadoras (2019)
The present investigation was proposed to determine the incidence of the margin of contribution in the management decisions of bakeries belonging to the city of Barranquilla. Department of the Atlantic - Colombia. For this, theoretical postulates of authors such as Robbins and Coulter (2007), Serna (2007), among others, were considered. The research was oriented under the positivist paradigm with quantitative approach and inductive empirical method. It was typified as explanatory with transversal design, of field; non-experimental, correlational - causal. The population was conformed by 1046 managers of small and medium bakery companies of Barranquilla - Atlántico, Colombia. To address the population studied, a directed sample was calculated, represented in two hundred and eighty-two (282) managers of bakery companies in the city of Barranquilla, Department of Atlántico - Colombia, to which the instrument designed to meet the objectives of the investigation. The data was collected through surveys, using a questionnaire with 52 items addressed to the managers and three response alternatives; always, sometimes, never. The content validity was obtained by consulting the opinion of 5 experts, while the reliability of the instrument was calculated by means of the Cronbach's Alpha coefficient and it showed a 0.95 points considered very high according to the scale of Ruiz (2015). The analysis of the data was oriented by descriptive statistics through the analysis of arithmetic frequencies and means used to describe the variables; and inferential statistics with application of hypothesis tests Pearson coefficient to measure correlation and linear regression tests and unidirectional variance analysis to determine the incidence of the contribution margin variable in decision making. It was determined that there is a good linear correlation between the explanatory variables and the dependent variable. Likewise, in the face of the theoretical framework analyzed, it can be inferred that the degree of discipline with which the projection of the contribution margin is assumed directly influences successful decision-making.